Indagación sobre el origen del concepto de responsabilidad social empresarial - Castro Herrera, Romel Diego (Universidad Icesi, 2013)
Through the exploration of two current approaches to the concept of corporate social responsibility, this paper has three main objectives. First, it presents the origin of this concept, which is a theoretical construct that has had different meanings, definitions and interpretations. Second, it seeks to explain three basic understandings of corporate social responsibility in three areas of current discourse: management reports, advertising guidelines and theories of management. These understandings are strategic, sociopolitical and ethical; this last viewed as a response to the various interactions between society and corporations. The third objective is to show the complex nature of the concept of corporate social responsibility, the needs within organizations that this concept has generated and possible objections to its theoretical foundations. This research emphasizes the need to consider corporate social responsibility in an integrated manner, so that different understandings of corporate social responsibility can be developed within the management of corporations in order to generate a positive impact as much for the communities which they are a part of as for the corporations themselves. Finally, this research highlights a number of considerations that are epistemological, ethical, educational and political: epistemological, regarding the characteristics of administrative knowledge; ethical, with respect to self-interest as limiting the discourse of corporate social responsibility; educational, in regard to the challenges this concept poses to business schools, and political, relating to the limits the concept places on the power of organizations.
Mediante la exploración de dos enfoques actuales sobre el concepto de Responsabilidad Social Empresarial, este trabajo pretende tres objetivos fundamentales. Primero, presentar el origen del concepto de Responsabilidad Social Empresarial, es decir, abordar el concepto como una construcción teórica que ha tenido diversas acepciones, definiciones e interpretaciones. Segundo, explicar las tres concepciones fundamentales de la Responsabilidad Social Empresarial en los discursos actuales, en los informes de gestión, en las pautas publicitarias y en las teorías administrativas; dichas concepciones son: el concepto estratégico, el concepto político-social y el concepto ético de la Responsabilidad Social Empresarial como una respuesta a las diversas interacciones entre la sociedad y las corporaciones. El tercer objetivo consiste en mostrar la naturaleza compleja del concepto, las necesidades que ha generado al interior de las organizaciones y las objeciones posibles a sus fundamentos teóricos. Esta indagación evidencia la necesidad de pensar la Responsabilidad Social Empresarial de forma integral, de tal manera que las diversas concepciones se articulen con la gestión de las organizaciones, con el fin generar un impacto favorable tanto para las comunidades en las que están insertadas las organizaciones como para las empresas mismas. Finalmente, esta indagación aporta una serie de consideraciones desde diversas categorías: epistemológica, sobre los rasgos del saber administrativo; ética, sobre el interés como límite del discurso de la Responsabilidad Social Empresarial; pedagógica como desafío a las escuelas de negocios; y política como limitación al poder de las organizaciones.
Keywords: T658.408/C355i/; Facultad de Ciencias Administrativas y Económicas; Producción intelectual registrada - Universidad Icesi; Administración; Responsabilidad social de las empresas; Stakeholders; Corporate social responsibility; Ethical behavior; strategic vision